Adam of the road - Vining, Elizabeth Gray, 1902-1999.; Lawson, Robert, 1892-1957 (New York, N.Y., U.S.A. : Puffin Books, 1987)
The adventures of eleven-year-old Adam as he travels the open roads of thirteenth-century England searching for his missing father, a minstrel, and his stolen red spaniel, Nick.
Originally published: New York : Viking Press, 1942.
Keywords: Minstrels -- Fiction; Newbery Medal; Middle Ages -- Fiction; England -- Fiction